Atopic skin diathesis rather than atopic dermatitis is associated with specific contact allergies. (15th February 2021) - Forkel, Susann; Cevik, Naciye; Schill, Tillmann; Worm, Margitta; Mahler, Vera; Weisshaar, Elke; Vieluf, Dieter; Pfützner, Wolfgang; Löffler, Harald; Schön, Michael P.; Geier, Johannes; Buhl, Timo
Summary: Background: The association of atopic dermatitis (AD) and allergic contact dermatitis has been a matter of considerable uncertainty. Study results range from lack of any association to increased sensitization for multiple allergens, but fail to identify consistent allergen associations. Objective: We studied a large patch test cohort of patients stratified by their atopic skin diathesis using the Erlangen Atopy Score (EAS), independent of active skin disease. Methods: Retrospective multi‐center data analysis from five departments of dermatology in Germany with 4, 509 patients. Patients were grouped as "no atopic skin diathesis" (n = 2, 165) and "atopic skin diathesis" (n = 1, 743), according to EAS. Results: Significantly more individuals with atopic skin diathesis showed at least one positive patch test reaction to the baseline series compared to individuals without atopic skin diathesis (49.1 % vs. 38.3 %). In logistic regression analyses, atopic skin diathesis was associated with a significantly higher risk of sensitization to methylchloroisothiazolinone/methylisothiazolinone (OR 2.383) and methylisothiazolinone (OR 1.891), thiuram mix (OR 1.614), as well as nickel (OR 1.530), cobalt (OR 1.683), and chromium (OR 2.089). Conclusions: Atopic skin diathesis proved to be the most important intrinsic risk factor for contact sensitization to few, specific allergens. Past or present AD was a less relevant variable.